Negative Consequences of the Use of Chemical Fertilizers in Agriculture of the Uzbek SSR - kizi, Khasanboeva Gulkhayo Khimmat (American Journal of Biodiversity, 2025)
Based on the fact that the use of excessive chemical fertilizer in the agriculture of the Uzbek SSR under the Soviet era led to socio-ecological consequences this study analyzes the negative effects of it. Previous research about the role of cotton monoculture in economic growth has been insufficiently concerned with the environmental or pública de saúde longterm consequences. The article employs the historical-analytical method and its sources remain archival records and statistical data, present how reliance on toxic substances such as butifos and pesticides adversely affected the soil, air, water and human population health. Studies show that 99 percent of chemical use does damage at the ecosystem and human being, contributing to increasing mortality, birth deformations and ecological degradation. The results highlight the critical need for a restructuring of past agricultural strategy and a switch towards more sustainable approaches. The findings of this study complement the central literature on the historical conditions of environmental challenges in Uzbekistan and provide suggestions for the development of future eco-conscious policies.